Strategi Manajemen Pemasaran Pada UMKM RW 11 Semolowaru Menggunakan Metode Analisis SWOT Guna Meningkatkan Daya Saing - Dwivina, Tessa Mirella; Salsabila, Ainan Salsabila; Anugrah P, RA. Bulan (Universitas Islam Negeri Sjech M. Djamil Djambek Bukittinggi, 2023)
ABSTRACTUMKM play a vital role in societal welfare, focusing on improving marketing management for increased sales. The research aims to create a practical management model supporting MSME productivity and development. Comprehensive training in business aspects, including marketing, production, HR, and finance, is crucial for UMKM. Continuous monitoring is necessary in their journey, utilizing SWOT analysis to determine marketing strategies and adapt to the business environment. The analysis assesses internal factors (Strengths and Weaknesses) and external factors or competitors (Opportunities and Threats). Identifying a lack of knowledge, the study recommends comprehensive training in all aspects. Four marketing strategies are proposed: S-O Strategy advocates product innovation and aggressive promotions with online sales. In the W-O strategy, attention to market needs and human resource quality is emphasized. The S-T strategy highlights product features and promotion innovation. In the W-T strategy, targeting markets, adapting to consumer wishes, and product adjustments are crucial for UMKM competitiveness.